The feasibility and effectiveness of thoracoscopic transdiaphragmatic approach for lung biopsy in rabbits. A randomized study - Wittmaack, Monica Carolina Nery [UNESP]; Barros, Felipe Farias Pereira da Câmara; Silva, Paloma Do Espírito Santo [UNESP]; Matsui, Andresa [UNESP]; Sembenelli, Guilherme [UNESP]; Mariano, Renata Sitta Gomes [UNESP]; Teixeira, Pedro Paulo Maia; Moraes, Paola Castro [UNESP] (FapUNIFESP (SciELO), 2020)
Purpose: To assess the feasibility of thoracoscopic transdiaphragmatic approach for biopsy of all lung lobes and to determine the optimal intercostal space (ICS) for biopsy of each lung lobe. Methods: Ten rabbits were positioned in dorsal recumbency. Total thoracoscopy lung biopsy was made combined transdiaphragmatic approach and right ICS approaches. A camera port was made in the transdiaphragmatic approach and the instrument port was made of ICS 7 and ICS 9. A pre tied loop ligature was placed to performed a caudal lung lobe biopsy and to simulate biopsies of the others lung lobes. Results: Biopsy of the cranial aspect of the right caudal lung lobe was performed at ICS 9. Simulated biopsy of the accessory lung lobe was performed at ICS 9. Simulated lung biopsy of the right cranial and middle lung lobes was performed at ICS 7. The caudal and dorsal aspect of the right caudal lung lobe was not visualized by telescope at transdiaphragmatic approach, and biopsy was not performed. Conclusions: Thoracoscopic transdiaphragmatic approach for lung lobes biopsies was a feasible technique, except for the caudal aspect of the right caudal lung lobe. An ideal intercostal port for biopsy of each right lung lobe was determined.
Keywords: Biopsy; Lung; Minimally Invasive Surgical Procedures; Rabbits; Thoracic Surgery, Video-Assisted